2020
DOI: 10.15446/agron.colomb.v38n1.78957
|View full text |Cite
|
Sign up to set email alerts
|

Biomass of Crotalaria juncea as a function of plant densities in the semiarid region of Northeastern Brazil

Abstract: An increase in the production per area of sunn hemp (Crotalaria juncea L.) biomass in order to expand its beneficial effects as green manure is an objective for the agronomic management of this species. Three experiments were performed during consecutive years to test the following plant densities per m-2: 10, 20, 30, and 40; 25, 35, 50, and 100; 25, 50, 75, and 100. For each density the spacing between the sowing rows and withinthe rows was equal. The experiments were conducted at Mossoro, RN, Brazil, with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
(52 reference statements)
0
4
0
1
Order By: Relevance
“…Information on how sunn hemp plant density influences its growth and biomass is vital for optimizing living mulch benefits (de Oliveira Miranda et al, 2020). In this study, the evaluation of sunn hemp at three plant densities showed that D2 (32.1 plants m −2 ) and D3 (48.1 plants m −2 ) resulted in the highest biomass accumulation when compared to D1 (16.1 plants m −2 ) (Figures 4C,D).…”
Section: Sunn Hemp Performancementioning
confidence: 65%
See 3 more Smart Citations
“…Information on how sunn hemp plant density influences its growth and biomass is vital for optimizing living mulch benefits (de Oliveira Miranda et al, 2020). In this study, the evaluation of sunn hemp at three plant densities showed that D2 (32.1 plants m −2 ) and D3 (48.1 plants m −2 ) resulted in the highest biomass accumulation when compared to D1 (16.1 plants m −2 ) (Figures 4C,D).…”
Section: Sunn Hemp Performancementioning
confidence: 65%
“…Figures 2A,B showed that the mean temperatures dropped in both growing seasons when the P3 living mulches were planted. Sunn hemp development and biomass production is influenced by the interaction of photoperiod and temperature, as well as planting period (de Oliveira Miranda et al, 2020;Subrahmaniyan et al, 2021). Dropping temperatures observed at late planting in the growing season and the association with shortening day lengths could have been the main causes of a decrease in biomass production in P3.…”
Section: Sunn Hemp Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Междурядья необходимы не более 10-20 см. Рекомендовано выращивание до 48-100 растений на 1 м 2 (33,34). При производстве бумаги, где требуется тонкое волокна, расстояние между рядами можно увеличить до 30-36 см (21).…”
Section: рис 2 географическое распространение культуры Crotalaria Jun...unclassified